Assessing determinants of Augmented Reality Applications - The IKEA Place example - Aguilar, Rita Frederico Festa Mendes da Silva (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Marketing Intelligence